THE INFLUENCE OF ORGANIZATIONAL CULTURE, QUALITY OF HUMAN RESOURCES AND LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE AT PT. PROVICES INDONESIA - Fikri Amarullah; Okder Pendrian (Jurnal Scientia, 2023)
Human resources are an important asset for the company because of their role as the subject of implementation of the company's activities. Organizational culture provides characteristics and identity to a company and is also the foundation for the company itself. The leadership style that is considered appropriate to the situation and conditions of the company will encourage employees to continue to be productive. This study aims to determine the effect of Organizational Culture, Quality of Human Resources, and Leadership Style on Employee Performance. In company operations, employee performance has an influence on achieving company goals so that it can continue to grow and develop. This type of research uses quantitative methods, where the data collected and obtained comes from PT Provices Indonesia as the object of research. Variable used in this study are Organizational Culture, Quality of Human Resources, and Leadership Style which act as independent variables and Employee Performance which act as the dependent variable. This research test was processed using SmartPLS. The results of the hypothesis test show that there is a positive and significant influence of the independent and dependent variables. The results of the evaluation of the coefficient of determination show that the Employee Performance variable can be explained by Organizational Culture, HR Quality, and Leadership Style variables by 69%. PT Provices must maintain the current Organizational Culture, Quality of HR, and Leadership Style because based on the assumption that the majority of respondents give a positive response to those already in the company so that employee performance is expected to remain good & productive.